Profil Metabolik Rumen In Vitro Pakan Silase Kulit Ubi Kayu dari Berbagai Lama Penyimpanan - Raguati, Raguati; Afzalani Afzalani; Rahmi Dianita; Yun Alwi; Atika Oktaliza (Buletin Peternakan Tropis, 2024)
This research aims to determine how long cassava peel silage can be stored while maintaining its fermentability in the rumen and its suitability as animal feed. The study was conducted at the Laboratory of Animal Nutrition and Forage, Faculty of Animal Science, University of Jambi. The material used in the research was cassava peel silage, molasses, EM4, and water. The study used a design with four treatments and five replications: P0 - silage without storage, P1 - silage stored for one week, P2 - silage stored for two weeks, and P3 - silage stored for three weeks. The variables observed in this study were pH, total gas, dry matter digestibility (DMD), organic matter digestibility (OMD), VFA, and microbial protein (MP). Data analysis was performed using the SPSS program, and if there was a significant difference between treatments, Duncan's test was carried out. The results showed that the treatment had a significant effect (P<0.05) on pH and an insignificant effect (P>0.05) on DMD, OMD, gas production, VFA, and microbial protein (MP). Based on the average results of the research, which were pH 6.25-6.71, DMD 66.47-72.19%, OMD 74.45-78.38%, total gas 69.00-76.80 ml, VFA 0.729-1.149 µM, and MP 481.080-526.220 mg/g. It can be concluded that cassava peel silage can be stored for up to three weeks without interfering with rumen metabolisms.